Generating High-Resolution Textures for 3D Virtual Environments using View-Independent Texture Mapping - Poullis, C.; Suya You; Neumann, U. (2007 IEEE International Conference on Multimedia and Expo, 2007)
Image based modeling and rendering techniques have become increasingly popular for creating and visualizing 3D models from a set of images. Typically, these techniques depend on view-dependent texture mapping to render the textured 3D models in which the texture of novel views is synthesized at runtime according to different view-points. This is computationally expensive and limits their application in domains where efficient computations are required, such as games and virtual reality. In this paper we present an offline technique for creating view-independent texture atlases for 3D models, given a set of registered images. The best texture map resolution is computed by considering the areas of the projected polygons in the images. Texture maps are generated by a weighted composition of all available image information in the scene.Assuming that all surfaces of the model are exhibiting Lambertian reflectance properties, ray-tracing is then employed, for creating the view-independent texture maps. Finally, all the generated texture maps are packed into texture atlases. The result is a 3D model with an associated view-independent texture atlas which can be used efficiently in any application without any knowledge of camera pose information.